Incidence of malignant disease in childhood: a 24-year review of the Manchester Children's Tumour Registry data. - Birch, J. M. (Nature Publishing Group, 1980)
The Manchester Children's Tumour Registry data for the period 1954-1977 have been analysed. The overall incidence of malignant disease in children aged 0-14 years in the north-west of England is estimated to be 100 per million person-years. The most common disease group is leukaemia, which forms about one third of the total number of cases. Among solid tumours, by far the most common presenting site is the central nervous system, representing nearly a quarter of all neoplasms. Wilms' tumour, neuroblastoma and soft-tissue sarcomas comprise approximately 5%, 6.5% and 6% respectively of the total. The tumours most frequently seen in adults (e.g. carcinoma of colon, lung and breast) are extremely rare in childhood. A significant excess of males was seen in acute lymphoid leukaemia, non-Hodgkin's lymphoma, Hodgkin's disease, medulloblastoma and hepatoblastoma. A female excess was found among germ-cell tumours. During the study period significant increases in incidence were seen among acute lymphoid leukaemia and epithelial tumours, and an increase in germ cell tumours approached significance.